The immediate impact of a balanced, very low-calorie diet on the metabolic health of Indian subjects - A prospective longitudinal study - Neeta Deshpande; A.H. Mamata; Reshma Parmaj; Sanjay Agarwal; Archana Sarda; Anjali Bhatt; Shilpa Joshi; Nitin Kapoor (Elsevier, 2023)
Problems considered: Global challenges posed by obesity, type 2 diabetes mellitus (T2DM), hypertension, and related metabolic diseases necessitate effective interventions. Pharmacotherapy often falls short, leading to a demand for innovative approaches. This study delves into the effects of an organized diet featuring a readily available food substitute blend over an eight-week span. Methods: The study implemented a low-calorie diet (800-830 calories), comprising three shakes, non-starchy vegetables, soups, reduced buttermilk, and limited fat. Assessments covered NCDs like T2DM, hypertension, dyslipidemia, and non-alcoholic fatty liver disease. WHO STEPS protocol guided anthropometric measures and blood pressure readings, while INBODY 230 Analyser determined body composition. SPSS 16 software facilitated analysis of baseline and two-month follow-up data. Results: Participants with an average baseline BMI of 31.9 kg/m2 witnessed substantial improvements. Weight, BMI, waist and hip circumferences, neck, arm, and thigh circumferences, and body fat percentage registered significant decreases. Positive changes were observed in diabetes indicators, including reduced HbA1c (7.2%-6.1%) and fasting/post-prandial blood glucose (p < 0.001). Noteworthy enhancements extended to blood pressure, triglycerides, and NAFLD markers (p < 0.001), indicating favorable shifts in obesity-related markers and metabolic irregularities. Conclusion: The study underscores the potential of reversal diet in real-world clinical settings, offering promise in ameliorating metabolic disorders linked to obesity. Intriguingly, these benefits extended to individuals of South Asian region, accentuating its broad relevance. However, sustaining these improvements necessitates further exploration through extended interventions with larger participant cohorts. The findings kindle optimism in addressing mounting burden of metabolic diseases on a global scale.